1993
DOI: 10.1111/j.1365-3040.1996.tb02052.x
|View full text |Cite
|
Sign up to set email alerts
|

Sink strength: Established and regulated by plant growth regulators

Abstract: Sink strength or sink activity is considered here to be the rate of uptake of source-derived organic compounds and can be expressed in terms of the amount of sink-directed assimilates as a percentage of the total of newly produced assimilates. I emphasize that many studies on sink activity actually deal with sink capacity; care is needed to avoid confusion. Plants growing at more or less optimal conditions perform a pattern of dry matter distribution which is determined by their genetic background, experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 7 publications
(4 reference statements)
0
42
0
2
Order By: Relevance
“…plumule and radicle of embryo in pre-soaked seed treatments could change the direction of assimilate transport and synthesis of auxin, gibberellin and ethylene in shoot and root meristems inverting the source-sink relationship in favour of shoot growth (Kuiper, 1993;Sakakibara et al, 2006). Fast growing roots act as strong sink for food reserves and grow at the expense of shoot growth.…”
Section: Resultsmentioning
confidence: 99%
“…plumule and radicle of embryo in pre-soaked seed treatments could change the direction of assimilate transport and synthesis of auxin, gibberellin and ethylene in shoot and root meristems inverting the source-sink relationship in favour of shoot growth (Kuiper, 1993;Sakakibara et al, 2006). Fast growing roots act as strong sink for food reserves and grow at the expense of shoot growth.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence supports a role in nutrient signaling to coordinate metabolic processes between sink and source tissues (Argueso et al, 2009). Moreover, cytokinins stimulate photosynthesis (Wareing et al, 1968) and are able to establish local metabolic sinks or enhance sink strength (Kuiper, 1993;Guivarc'h et al, 2002). The effect on sink strength has also been demonstrated in 35S-CKX1-overexpressing tobacco (Nicotiana tabacum) plants, in which decreased cytokinin levels reduced the sink strength of the shoot (Werner et al, 2008).…”
mentioning
confidence: 93%
“…The ability of CKs to increase sink capacity has been associated with their role in growth, through the control of cell division (Kuiper, 1993;Werner et al, 2008), photosynthesis (Paul Figure 6. Protein stability and oxidation of wild-type (WT) and transgenic P SARK ::IPT rice plants.…”
Section: Gs Nadh-gogat Gdh Amination [Gdh a ] And Deamination [Gdh mentioning
confidence: 99%
“…Cytokinins (CKs) have been shown to regulate plant cell differentiation, leaf senescence, and other key developmental processes (Sakakibara, 2006). It has also been shown that CKs regulate assimilate partitioning (Ronzhina and Mokronosov, 1994), sink strength (Kuiper, 1993), and source/sink relationships (Roitsch, 1999). The localized expression in tobacco (Nicotiana tabacum) of a promoterless ISOPENTENYLTRANSFERASE (IPT), a gene encoding the enzyme that catalyzes the rate-limiting step in CK synthesis, enhanced the local sink strength and quickly mobilized nutrients to the tissues with elevated CK (Guivarc'h et al, 2002).…”
mentioning
confidence: 99%